Pseudomonas aeruginosa lasR Transcription Correlates with the Transcription of lasA, lasB, and toxA in Chronic Lung Infections Associated with Cystic Fibrosis - Storey, Douglas G. (American Society for Microbiology, 1998)
The role of Pseudomonas aeruginosa quorum-sensing systems in the lung infections associated with cystic fibrosis (CF) has not been examined. The purpose of this study was to determine if genes regulated by the LasR-LasI quorum-sensing system were coordinately regulated by the P. aeruginosa populations during the lung infections associated with CF. We also wanted to ascertain if there was a relationship between the expression of lasR, a transcriptional regulator, and some P. aeruginosa virulence factors during these infections. We extracted RNAs from the bacterial populations of 131 sputa taken from 23 CF patients. These RNAs were blotted and hybridized with probes to P. aeruginosa lasA, lasB, and toxA. The hybridization signals from each probe were ranked, and the rankings were analyzed by a Spearman rank correlation to determine if there was an association between the population transcript accumulations for the three genes. The correlations between the transcript accumulation patterns of pairs of the genes suggested that lasA, lasB, and toxA might be coordinately regulated during CF lung infections. To determine if this coordinate regulation might be due to regulation by LasR, we probed RNAs, extracted from 84 sputa, with the lasR, lasA, lasB, toxA, and algD probes. Statistical analysis indicated that lasR transcript accumulation correlated to lasA, lasB, toxA, and algD transcript accumulations. These results indicated that lasR may at least partially regulate or be coordinately regulated with lasA, lasB, toxA, and algD during the lung infections associated with CF. These results also suggested that the LasR-LasI quorum-sensing system may control the expression of at least some virulence factors in the lungs of patients with CF.